Disney+ : pricing and strategy - Robson, Karen, (SAGE Business. Cases., 2022)
Disney is one of the leading entertainment companies in the world. Towards the end of 2019, it launched a streaming service called Disney+. The service has proven enormously popular: less than one year after its launch, Disney+ has already achieved its five-year goal with respect to registered users. In 2020, Disney added a premium tier to its streaming service called Premier Access, which users could purchase to get early access to Disney's premium content: the live action remake of Mulan (initially intended for theatrical release). This case provides an opportunity for students to understand and assess how the marketing environment impacts strategic decision-making in marketing. In addition, this case provides information on the pricing strategy implemented by Disney, which students can use to better understand strategies available when pricing new offerings.